Journal of Academic Ethics - Poff CM, PhD, Deborah C.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
The Journal of Academic Ethics is a multidisciplinary and interdisciplinary, peer reviewed journal which examines all ethical issues which arise within the scope of university purposes. The journal publishes original research in the ethics of research production and publication; teaching and student relations; leadership; management and governance. The journal offers sustained inquiry into such topics as the ethics of university strategic directions; ethical investments; sustainability practices; the responsible conduct of research and teaching; collegiality and faculty relations; and the appropriate models of ethical and accountable governance for universities in the 21st century.
Keywords: Ethics; School management and organization; School administration; Administration, Organization and Leadership; Ethics